Distribution of Pain Phenotypes and Their Associations with Clinical, Psychological, and Quality-of-Life Outcomes in Plantar Fasciitis: A Cross-Sectional Study - Bilal Uysal; Ender Salbaş; Nilay Şahin (Bolu Abant Izzet Baysal Universitesi Tip Fakultesi Abant Tip Dergisi, 2026)
Background: Plantar fasciitis is traditionally considered a predominantly nociceptive disorder; however, chronic plantar heel pain may include neuropathic-like and nociplastic features that influence clinical presentation and outcomes. This study aimed to describe the distribution of pain phenotypes in patients with plantar fasciitis and to compare clinical, psychological, functional, and quality-of-life outcomes across phenotypes. Methods: In this prospectively recruited cross-sectional study, 100 adults with clinically diagnosed plantar fasciitis of at least three months' duration were classified using a hierarchical phenotype algorithm. Neuropathic-like features were identified using the Douleur Neuropathique 4 questionnaire (DN4 ≥4). Among patients not meeting this criterion, nociplastic features were classified according to clinical criteria for nociplastic musculoskeletal pain; remaining patients were classified as predominantly nociceptive. Outcomes included pain intensity, heel tenderness, pain catastrophizing, depressive symptoms, central sensitization, foot function, and SF-12 raw physical and mental composite scores. Results: Thirty-six patients were classified as nociceptive, 31 as neuropathic-like, and 33 as nociplastic. Pain intensity did not differ significantly between groups. In contrast, the neuropathic-like and nociplastic groups showed higher central sensitization and depressive symptom scores and lower SF-12 physical and mental composite scores than the nociceptive group. The neuropathic-like group also showed greater heel tenderness and worse foot function. Age- and sex-adjusted regression models supported independent associations between non-nociceptive phenotypes and several adverse patient-reported outcomes, particularly central sensitization and depressive symptoms. Conclusions: Pain phenotypes in plantar fasciitis are heterogeneous. Identifying neuropathic-like and nociplastic features may improve clinical assessment and support more individualized, mechanism-informed management strategies.